Application of a 3-dimensional printed navigation template in Bernese periacetabular osteotomies: A cadaveric study. Issue 50 (December 2016) - Zhou, You; Kang, Xiaopeng; Li, Chuan; Xu, Xiaoshan; Li, Rong; Wang, Jun; Li, Wei; Luo, Haotian; Lu, Sheng
Abstract : Abstract: The aim of the present study was to describe the application of 3D printed templates for intraoperative navigation and simulation of periacetabular osteotomies (PAOs) in a cadaveric model. Five cadaveric specimens (10 sides) underwent thin-slice computed tomographic scans of the ala of ilium downwards to the proximal end of femoral shaft. Bernese PAO was performed. Using Mimics v10.1 software (Materialise, Leuven, Belgium), 3D computed tomographic reconstructions were created and the 4 standard PAO bone cuts—ischial, pubic, anterior, and posterior aspects of the ilium—as well as rotation of the dislocated acetabular bone blocks were simulated for each specimen. Using these data, custom 3D printed bone-drilling templates of the pelvis were manufactured, to guide surgical placement of the PAO bone cuts. An angle fix wedge was designed and printed, to help accurately achieve the predetermined rotation angle of the acetabular bone block. Each specimen underwent a conventional PAO. Preoperative, postsimulation, and postoperative lateral center-edge angles, acetabular indices, extrusion indices, and femoral head coverage were measured and compared; P and t values were calculated for above-mentioned measurements while comparing preoperative and postoperative data, and also in postsimulation and postoperative data comparison. All 10 PAO osteotomies were successfully completed using the 3D printed bone-drilling template and angle fix wedge. No osteotomy entered the hip joint and a single posterior column fracture was observed. Comparison of preoperative and postoperative measurements of the 10 sides showed statistically significant changes, whereas no statistically significant differences between postsimulation and postoperative values were noted, demonstrating the accuracy and utility of the 3D printed templates. The application of patient-specific 3D printed bone-drilling and rotation templates in PAO is feasible and may facilitate improved clinical outcomes, through the use of precise presurgical planning and reduced surgical complications with the precisely guided bone drilling.